USE OF THE BACTERIAL NAMES ANAYSIS ACCORDING TO HISTORICAL AND ETYMOLOGICAL ASPECTS TO FACILITATE THE MEMORIZATION - sudibya, akhmad (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2014)
Medical students should know two aspects of every bacterial names. The two aspects are etymological aspect and historical aspect. Knowledge of these aspects would facilitate the students in memorizing bacterial names.